2000
DOI: 10.1038/76282
|View full text |Cite
|
Sign up to set email alerts
|

Complete reversal of fatal pulmonary hypertension in rats by a serine elastase inhibitor

Abstract: Progression of pulmonary hypertension is associated with increased serine elastase activity and the proteinase-dependent deposition of the extracellular matrix smooth muscle cell survival factor tenascin-C (refs. 1,2). Tenascin-C amplifies the response of smooth muscle cells to growth factors, which are also liberated through matrix proteolysis. Recent organ culture studies using hypertrophied rat pulmonary arteries have shown that elastase inhibitors suppress tenascin-C and induce smooth muscle cell apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
251
4
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(271 citation statements)
references
References 17 publications
9
251
4
7
Order By: Relevance
“…Membrane type-1-MMP was also expressed in endothelial and myofibroblastic cells of concentric and plexiform lesions. These results and those in the monocrotaline model suggest that the inhibition of elastases or MMPs might be beneficial in IPAH as demonstrated in the monocrotaline model of PH [65], potentially leading to the apoptosis of smooth muscle cells.…”
Section: Pathobiologysupporting
confidence: 55%
See 1 more Smart Citation
“…Membrane type-1-MMP was also expressed in endothelial and myofibroblastic cells of concentric and plexiform lesions. These results and those in the monocrotaline model suggest that the inhibition of elastases or MMPs might be beneficial in IPAH as demonstrated in the monocrotaline model of PH [65], potentially leading to the apoptosis of smooth muscle cells.…”
Section: Pathobiologysupporting
confidence: 55%
“…In fact, 'apoptosis-resistance' might play a central role in both the endothelial-and smooth muscle cell-based pulmonary vascular lesions [66], since IPAH lungs have lower number of apoptotic cells than normal or emphysematous lungs [67]. As growth signals originated by PDGF, TGF-β, EGF, serotonin, and extracellular matrix proteins are interrupted in animal models of PH, pulmonary arteries undergo de-remodeling associated with apoptosis of pulmonary artery smooth muscle cells [65]. Targeting apoptosis of the hypertrophic smooth muscle cells might represent a more viable approach towards treatment.…”
Section: Pathobiologymentioning
confidence: 99%
“…13,15 In five of these models, 28,50,52,54 elafin was used as the elastase inhibitor, given as an infusion, 28 by gene therapy 50,52 or in an overexpressing transgenic mouse. 14,49,54 Elafin is a small, 9-kDa protein, first described in association with inflammatory lesions in the airways 55 and with psoriasis in skin.…”
Section: Grade Imentioning
confidence: 99%
“…7 Fragmentation of PA elastin has been observed in PAs of PAH patients, 11 and heightened activity of a serine elastase has been identified in the PA in a variety of experimental forms of PAH [12][13][14][15] and in cultured PA smooth muscle cells (SMC). 16 -19 Moreover, inhibition of this elastase can attenuate or prevent [12][13][14] and even reverse 15 experimental pulmonary vascular disease in rodents. In all rodent models where elastase inhibitors were used, the pulmonary vascular lesions were characterized by loss or increased muscularization of normally nonmuscular peripheral arteries at the alveolar wall and duct level, and medial hypertrophy of proximal muscular arteries.…”
mentioning
confidence: 99%
“…As is well known, excessive proliferation and apoptosis resistance of pulmonary artery smooth muscle cells (PASMCs) in small pulmonary arteries could cause pulmonary arterial remodeling under hypoxia,16 yet during reoxygenation, the thickened medial layer could gradually reverse 11, 13. More importantly, previous studies indicated that inducing PASMC apoptosis could prevent and reverse established pulmonary vascular remodeling 17, 18, 19. However, whether increased apoptosis of PASMCs participated in the reversal of pulmonary arterial remodeling during reoxygenation has not been clarified.…”
Section: Introductionmentioning
confidence: 99%